Conductive Coating: Sprayable, Superhydrophobic, Electrically, and Thermally Conductive Coating (Adv. Mater. Interfaces 2/2021). Issue 2 (22nd January 2021) - Baldelli, Alberto; Ou, Junfei; Barona, David; Li, Wen; Amirfazli, A.
Abstract : A simple to make, multifunctional, heatable and sprayable superhydrophobic and electrically conductive coating is developed. The coating is made of carbon nanofibers dispersed in a polymer matrix. It is capable of melting ice and repelling water at the same time reaching temperatures as high as 140 °C for a dry coating. More details can be found in article number 1902110 by Wen Li, A. Amirfazli, and co‐workers.